Lignocellulosic ethanol production combined with CCS—A study of GHG reductions and potential environmental trade‐offs. Issue 2 (1st December 2020) - Lask, Jan; Rukavina, Slavica; Zorić, Ivana; Kam, Jason; Kiesel, Andreas; Lewandowski, Iris; Wagner, Moritz
Abstract: The combination of bioethanol production and carbon capture and storage technologies (BECCS) is considered an indispensable method for the achievement of the targets set by the Paris agreement. In Croatia, a first‐of‐its‐kind biorefinery project is currently underway that aims to integrate a second‐generation ethanol plant into an existing fossil refinery. The goal is to replace the fossil fuel production by second‐generation ethanol production using miscanthus. In the ethanol fermentation, CO2 is emitted in highly concentrated form and this can be directly compressed, injected and stored in exploited oil reservoirs. This study presents an assessment of the greenhouse gas (GHG) reduction potential of miscanthus ethanol produced in combination with CCS technology, based on data from the planning process of this biorefinery project. The GHG reduction potential is evaluated as part of a full environmental life cycle assessment. This is of particular relevance as a lignocellulosic ethanol industry is currently emerging in the European Union (EU) and LCAs of BECCS systems have, so far, often omitted environmental impacts other than GHG emissions. Overall, the ethanol to be produced in this planned biorefinery project would clearly achieve the EU's global warming potential (GWP) reduction target for biofuels. Depending on the accounting approach applied for the biological carbon storage, reduction potentials between 104% and 138% relative to the fossil comparator are likely. In addition, ethanol can reduce risks to resource availability. As such, the results generated from data based on the intended biorefinery project support the two major rationales for biofuel use. However, these reductions could come at the expense of human health and ecosystem quality impacts associated with the combustion of lignin and biogas. In order to prevent potential environmental trade‐offs, it will be imperative to monitor and manage these emissions from residue combustion, as they represent significant drivers of the overall environmental impacts. Abstract : The combination of bioethanol production and carbon capture and storage technologies (BECCS) is considered an indispensable method for the achievement of the targets set by the Paris agreement. In Croatia, a first‐of‐its‐kind BECCS project is currently underway. This study presents an assessment of the GHG reduction and potential environmental trade‐offs based on data from the project planning phase. The ethanol to be produced could achieve reduction potentials between 104% and 138% relative to petrol. However, these reductions could come at the expense of impacts on human health and ecosystem quality, which are often neglected in LCAs of bioenergy systems.